Temperature‐ and Ambient Pressure‐Independent Sensing of Hydrogen in Fluids Using Cascaded Interferometers Incorporated in Optical Fibers. Issue 6 (4th December 2022) - Lee, Sungjae; Ryu, Bowon; Kim, Inho; Song, Yong‐Won
Abstract: Practical gas sensors are indispensable for the healthy operation of cutting‐edge hydrogen‐based systems. An optical fiber‐based hydrogen sensor incorporating a robust Fabry–Perot interferometric structure on a fiber tip with high sensitivity, selectivity, and reliability of operation and a micrometer‐scale footprint is demonstrated. The hydrogen‐sensitive volume expansion of palladium provides bi‐metal operation with a silicon nitride mirror to tune the interferometer cavity and therefore the resonance modes by switching the mirror form factor from a flat to convex shape. It does not require any peripherals, including a power supply or data communication modules. In addition to fiber‐inherent advantages, such as remote and multiplexed monitoring without electromagnetic field interference, the sensor guarantees temperature‐ and pressure‐independent operation by adding a simple glass sub‐cavity and microwindows in the mirror layer, respectively. Critically, the sensor highlights reliable operation in a liquid fluid (electrical transformer oil) to monitor hydrogen as its "damage marker" escaping from a mechanical shield or selective gas screen. The detection limit, sensitivity, and response time of the sensor under atmospheric conditions are 15 ppm, 29.6 nm/%, and 12.5 s, respectively. In addition, the unimpaired operation of the sensor in 60 °C transformer oil is verified experimentally. Abstract : Temperature‐ and ambient pressure‐independent hydrogen sensor based on a cascaded interferometric structure embedded onto an optical fiber tip is fabricated and systematically analyzed. The hydrogen sensitivity of the sensor is dramatically elevated due to the novel design of flexible mirrors in the interferometric structure. A simple and robust sensor structure enables reliable operation in fluids including air and transformer oil.